The Interplay Between Supply Chain Transparency and NGO Pressure: A Quantitative Analysis in the Fashion Industry Context - Naemi Schäfer; Lars Petersen; Jacob Hörisch (Journal of Business Ethics, 2023)
Companies have been experiencing increasing pressure from NGOs to overcome unethical and unsustainable behaviours. The purpose of this research was to study the interplay between supply chain transparency and NGO pressure. The analysis builds on the literature on supply chain transparency and institutional pressures. We conducted a time-lagged, multi-level regression analysis that included data from 270 fashion companies over a 5-year period to investigate the effect of NGO pressure on transparency and vice versa. The results revealed that companies with higher levels of transparency are more likely to be pressured by NGOs than less transparent companies. Furthermore, our findings show that, depending on the number of campaigns, NGO power and communication about campaigns, NGO pressure can either stimulate corporate transparency or turn into a negative effect that leads to lower levels of transparency.
Keywords: 300; Supply chain transparency; Sustainability; NGO pressure; Quantitative analysis